Study of the Older Adults' Motivators and Barriers Engaging in a Nutrition and Resistance Exercise Intervention for Sarcopenia: An Embedded Qualitative Project in the MIlkMAN Pilot Study. (May 2020) - Dismore, Lorelle; Hurst, Christopher; Sayer, Avan A.; Stevenson, Emma; Aspray, Terry; Granic, Antoneta
Objectives: The present study aimed to investigate motivators and barriers to older adults engaging in a nutrition and resistance exercise (RE) intervention for sarcopenia.Methods: We conducted a content analysis of structured interviews with 29 community-dwelling older adults (aged 65–80 years) completing the MIlk Intervention Muscle AgeiNg (MIlkMAN) study.Results: Content analysis revealed that self-perceived improved health, knowledge acquisition in nutrition and exercise, social well-being, professional support in a fun environment, and positive reported outcomes were motivators for engagement in the intervention. Peer encouragement, social bonds, and their retention were motivators to continuing engagement after study completion, especially in widowed women. Barriers to maintenance included affordability, environmental factors, and concerns over negative health outcomes.Discussion : Nutrition and RE interventions for sarcopenia should focus on knowledge acquisition about their health benefits, being enjoyable, and offering social opportunities that have the potential to last beyond the study duration to promote and maintain positive health behaviors.